CAN MANUFACTURING OUTPUT SERVITIZATION REDUCE CARBON EMISSIONS? - Wang, Hongsen; He, Dongni (International Journal of Industrial Engineering: Theory, Applications and Practice, 2023)
Carbon emissions from manufacturing have been a growing global concern in recent years. The growth in manufacturing firms’ service output and its carbon emission reduction effect have received less attention, though. Using data from 2008-2020 for listed companies in China, this study empirically analyzed the effects of manufacturing output servitization on carbon intensity. The results revealed a significant negative relationship between them. Heterogeneity analysis finds that the carbon emission reduction effect of manufacturing servitization is strongest in (i) private and relatively small-scale firms and (ii) developed regions and capital-intensive industries. The mediating effect study shows that green TFP and revenue growth rate are the transmission channels for the environmental impact of manufacturing servitization. This study verifies that servitization is a feasible path to coordinate high-quality economic development with resource and environmental constraints from different perspectives to provide a reference for the realistic development of diverse economies.